Inter- und multidisziplinäre Perspektiven der Geschlechterforschung - Schnegg, Kordula; Tschuggnall, Julia; voithofer, caroline; Auer, Manfred (Innsbrucker Gender Lectures, 2022)
The 'INNSBRUCK GENDER LECTURES' are a discussion forum that enables the members of the Center Interdisciplinary Gender Studies Innsbruck (CGI), invited gender researchers and the interested public to explore and critically discuss controversial topics as well as to exchange ideas on theoretical foundations of interdisciplinary and multidisciplinary gender research. The authors of this volume are Gundula Ludwig, Michelle Cottier, Leonhard Dobusch, Ilona Horwath, Claudia Opitz-Belakhal and Elisabeth T. Sandler.